The Meaning and Components of Self-Directed Digital Learning Behavior among Senior Secondary School Students in Thailand - Na nan, Pattamaporn; Poonpol, Pitchayanee; Intraprasert, Dusadee (Journal of Inclusive and Innovative Education, 2025)
This study aimed to (1) understand and define the meaning of self-directed digital learning behavior, and (2) identify its key components of behavior among upper secondary school students in Thailand. A qualitative research methodology was employed to examine learners’ experiences and perspectives within authentic contexts. The participants included eight upper secondary school students with experience in learning through digital technology. Purposive sampling was used to select the participants, and data were collected through semi-structured interviews. The data were analyzed using qualitative content analysis, which involved transcription of interviews, iterative reading, coding, categorization, and synthesis of key themes. The findings revealed that (1) self-directed digital learning behavior refers to a structured process in which learners independently regulate their own learning. Learners define personal learning goals aimed at enhancing their knowledge, skills, and competencies according to their individual needs and future aspirations. They design personalized learning plans, select appropriate digital resources, critically evaluate the information obtained from digital media, and assess their own understanding of the content. (2)The study identified five key components of self-directed digital learning behavior: 1) goal setting, 2) learning planning, 3) digital media selection, 4) evaluation of digital information, and 5) comprehension monitoring. These findings serve as a conceptual framework that can be used for developing assessment tools and strategies to promote self-directed learning in the digital age.